Fulfillment of Victims’ Rights to Handling Child Victims of Sexual Violence in Buleleng Regency - Yuliartini, Ni Putu Rai; Mangku, Dewa Gede Sudika (Journal of Judicial Review, 2024)
This research aims For analyze fulfillment of victims' rights in Handling case child victims of violence sexual in Buleleng Regency. With use approach juridical-empirical, this research explores implementation of the legal protection provided to child victims of violence sexual, as well as evaluate effectiveness mechanism handling carried out by the party authorities, including apparatus enforcer law and child protection institutions. The results of this study indicate that although there is adequate regulation, still there is constraint in implementation, such as limitations source Power humans and their lack mentoring psychological. This research is expected can become input for maker policy For increase efforts to protect and fulfill the rights of children who are victims of violence sexual.